Application of business intelligence for inventory management and control - Pereira, Karolaine Cristina; Barbosa, Maria Luciene Borges; Santos, Aline Gonçalves dos; Fonseca Jr , Lázaro Antônio da (Brazilian Journal of Production Engineering, 2023)
The constant need of organizations to serve their customers with efficiency, effectiveness and agility, makes it necessary to develop good inventory management. Therefore, technological tools have been developed and used by organizations in the management of data related to inventory. Given this scenario, the present study was developed with the objective of creating an application for management and inventory control through the Business Intelligence tool (Power BI), with indicators that will show all inputs and outputs of inputs in real time in a food sector company. To identify the company’s needs, the sector’s routines were monitored and the way in which the managerial reports on incoming and outgoing goods were created were monitored. Thus, an application was developed in Power Apps Software to improve the process of capturing information related to stock, inputs and outputs. Power BI Software was used to monitor and analyze indicators and stock levels. Thus, it was observed that the application can provide an 80% reduction in the time spent posting inputs and outputs of items, in addition to reducing, by 33%, the time with checking items of higher purchase priority.